Dual‐Function of Cation‐Doping to Activate Cationic and Anionic Redox in a Mn‐Based Sodium‐Layered Oxide Cathode. Issue 24 (18th May 2022) - Ni, Qing; Zhao, Yongjie; Yuan, Xuanyi; Li, Jingbo; Jin, Haibo
Abstract: Recently, sodium‐ion batteries have shown great potential for energy storage owing to their favorable electrochemical properties and intrinsic cost performance, which fuels the research and development of Mn‐based layered oxides as promising sodium‐ion cathodes. However, the undesirable structural evolution and oxygen redox impose great challenge on the cycling stability and rate capability of such cathodes. In this work, it is reported that Fe and Al can effectively tailor the Na2/3 Mn2/3 Fe1/6 Al1/6 O2 to trigger a stable cationic and anionic redox behavior. In situ X‐ray diffraction analysis confirms the retention of a stable P2 phase upon cycling, and density functional theory results demonstrate that Al 3+ doping can strengthen the covalency of MnO bond. The Na2/3 Mn2/3 Fe1/6 Al1/6 O2 cathode can retain 90% of its initial capacity within the voltage range of 2.0–4.2 V versus Na + /Na at 200 mA g ‐1 after 100 cycles. Moreover, ex situ X‐ray photoelectron spectroscopy reveals that the specific capacity can be replenished by the synergistic reactions between Fe 3+ /Fe 4+ /Fe 3+ and O 2‐ /(O2 ) n ‐ pairs within the voltage range of 4.0–4.4 V versus Na + /Na, which is also elucidated by theoretical calculation. Abstract : In this work, it is proven that the capacity at the 4.2–4.4 V plateau is contributed to the synergistic redox of Fe 3+ /Fe 4+ /Fe 3+ accompany with O 2− /(O2 ) n − evolution based on a variety of characterizations and density functional theory calculation results. Besides, Jahn–Teller effect mainly caused by Mn 3+ in this P2 cathode is successfully suppressed via Al/Fe substitution due to the higher covalency of MnO bond. A stable crystal structure of FeAl‐NMO is achieved during cycling process because of the suppressed Jahn–Teller effect and the formation of a unique Fe(OO) species.